2010
DOI: 10.1111/j.1365-2486.2009.02006.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 increases microbial growth rates in soil: results of three CO2 enrichment experiments

Abstract: Increasing the belowground translocation of assimilated carbon by plants grown under elevated CO 2 can cause a shift in the structure and activity of the microbial community responsible for the turnover of organic matter in soil. We investigated the long-term effect of elevated CO 2 in the atmosphere on microbial biomass and specific growth rates in root-free and rhizosphere soil. The experiments were conducted under two free air carbon dioxide enrichment (FACE) systems: in Hohenheim and Braunschweig, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(82 citation statements)
references
References 69 publications
5
75
0
Order By: Relevance
“…These findings agree with a recent metaanalysis (15) and are most likely due to elevated soil moisture content (23), increased belowground translocation of assimilated carbon by plants (20,24,25), and increased above-and belowground litter input (9).…”
supporting
confidence: 91%
“…These findings agree with a recent metaanalysis (15) and are most likely due to elevated soil moisture content (23), increased belowground translocation of assimilated carbon by plants (20,24,25), and increased above-and belowground litter input (9).…”
supporting
confidence: 91%
“…As consequences, increased carbon input in turn significantly changed bacterial diversity, composition, and structure and increased the functional potential of bacterial communities for carbon degradation and nutrient cycling, although such effects differed across various ecosystems (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In contrast, fungal biomass and relative abundance of total microbial biomass did not change significantly under eCO 2 in this BioCON (biodiversity, CO 2 , and N deposition) experimental site (6,21).…”
mentioning
confidence: 73%
“…For example, no detectable effects of eCO 2 on microbial community structure, microbial activity, potential soil N mineralization or nitrification were observed at a sweetgum free-air CO 2 enrichment (FACE) experiment in TN, USA (Austin et al, 2009), whereas in a no-till wheat-soybean rotation agro-ecosystem, the community composition and structure significantly affected by eCO 2 but not by eO 3 or eCO 2 þ eO 3 (Cheng et al, 2011). Recently, more studies suggest that eCO 2 and/or eO 3 significantly alter microbial community composition, structure, functional potential/activity, interaction network and/or dynamics (Lesaulnier et al, 2008;Blagodatskaya et al, 2010;Drigo et al, 2010;Feng et al, 2010;Zhou et al, 2010Zhou et al, , 2011He et al, 2010bHe et al, , 2012bDeng et al, 2012;Drigo et al, 2013;Li et al, 2013). In addition, it has been shown that the response of soil microbial comunities to global change factors may be directly or indirectly mediated by plant genotypes/cultivars, the diversity of plant assemblages and/or other environmental factors (Talhelm et al, 2009;Singh et al, 2010;Drigo et al, 2013;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%